Photosynthetic Cost Associated With Induced Defense to Plasmopara viticola in Grapevine - Nogueira Júnior, Antonio F.; Tränkner, Merle; Ribeiro, Rafael V.; von Tiedemann, Andreas; Amorim, Lilian (Frontiers in Plant Science, 2020)
Downy mildew caused by Plasmopara viticola is one of the most destructive diseases of Vitis vinifera worldwide. Grapevine breeding programs have introgressed P. viticola-resistant traits into cultivated V. vinifera genotypes and launched interspecific hybrids with resistance against downy mildew. In general, pathogen infection affects primary metabolism, reduces plant growth and development and modifies the secondary metabolism toward defense responses, which are costly in terms of carbon production and utilization. The objective of this work was to evaluate the photosynthesis impairment by inducible defenses at the leaf level in V. vinifera cultivars resistant to P. viticola. Photosynthetic limitations imposed by P. viticola in susceptible and resistant grapevine cultivars were evaluated. Histochemical localization of hydrogen peroxide and superoxide and the activity of ascorbate peroxidase were assessed. Measurements of leaf gas exchange, chlorophyll fluorescence and the response of leaf CO2 assimilation to increasing air CO2 concentrations were taken, and photosynthetic limitations determined in cultivars Solaris (resistant) and Riesling (susceptible). The net photosynthetic rates were reduced (−25%) in inoculated Solaris plants even before the appearance of cell death-like hypersensitive reactions (“HR”). One day after “HR” visualization, the net photosynthetic rate of Solaris was reduced by 57% compared with healthy plants. A similar pattern was noticed in resistant Cabernet Blanc and Phoenix plants. While the susceptible cultivars did not show any variation in leaf gas exchange before the appearance of visual symptoms, drastic reductions in net photosynthetic rate and stomatal conductance were found in diseased plants 12 days after inoculation. Decreases in the maximum Rubisco carboxylation rate and photochemical impairment were noticed in Riesling after inoculation with P. viticola, which were not found in Solaris. Damage to the photochemical reactions of photosynthesis was likely associated with the oxidative burst found in resistant cultivars within the first 24 h after inoculation. Both chlorophyll degradation and stomatal closure were also noticed in the incompatible interaction. Taken together, our data clearly revealed that the defense response against P. viticola causes a photosynthetic cost to grapevines, which is not reversible even 12 days after the pathogen infection.